«The New Poor» Scientists: Life Strategies Under Crisis - Лариса Евгеньевна Петрова (Journal of Economic Sociology, 2010)
A group of new poor is under focus in this paper. The new poor are a group of people who is experiencing a sharp decrease of their standards of living but still have the same professional status. A hypothesis of values’ influence on strategic behavior of scientists is tested relying on empirical data. The data source is the survey of employees of the scientific and production and scientific institutes in Moscow, Krasnodar, Nizny Novgorod and Yekaterinburg, held in the fall of 1998. The in-depth interviews were devoted to the current life situation of the studied group: working biography, job problems, family problems, future plans, macro environment’s characteristics.